Soluble urokinase plasminogen activator receptor as a prognostic marker of all-cause and cardiovascular mortality in a black population. (1st April 2015) - Botha, Shani; Fourie, Carla M.T.; Schutte, Rudolph; Eugen-Olsen, Jesper; Pretorius, Ronel; Schutte, Aletta E.
Abstract: Background: Elevated inflammatory markers such as C-reactive protein (CRP) and interleukin-6 (IL-6) are well-known risk factors for cardiovascular mortality. The less familiar marker, soluble urokinase plasminogen activator receptor (suPAR), is known to predict cancer, infections and all-cause mortality. We determined whether suPAR, CRP and IL-6 are predictive of both all-cause and cardiovascular mortality in a black population, highly burdened by cardiovascular disease and HIV infection. Methods: We included 1425 black South Africans, of which 208 died within five years after baseline data collection. EDTA plasma biomarker levels were determined, while all-cause and cardiovascular mortality were used as endpoints. Results: At baseline suPAR, CRP and IL-6 were higher in non-survivors than in survivors (P < 0.001). SuPAR (HR 1.27, 95% CI 1.09–1.48), IL-6 (HR 1.49, 95% CI 1.24–1.78) and CRP (HR 1.39, 95% CI 1.17–1.65) predicted all-cause mortality, while only suPAR (HR 1.40, 95% CI 1.04–1.87) and IL-6 (HR 1.61, 95% CI 1.10–2.35) predicted cardiovascular mortality. The prognostic value of suPAR was independent of IL-6 and CRP (P ≤ 0.015). Conclusion: SuPAR predicted both all-cause and cardiovascular mortality, independent of traditional risk factors, HIV and other inflammatory markers, underlining the prognostic value of suPAR in a black population. Graphical abstract: Highlights: It is unknown whether suPAR could predict mortality, especially in blacks. We investigated 1425 black South Africans of which 208 died. SuPAR, CRP and IL-6 were higher in non-survivors. SuPAR predicted both all-cause and cardiovascular mortality in blacks. This was independent of CRP, IL-6, HIV and other risk factors.